Temeljna načela i postupci u pretvaranju sirove dijalektološke građe u znanstveni rječnik - Blažeka, Đuro (Slavia Centralis, 2020)
Basic principles and procedures for turning raw dialectal materials into a scientific dictionary The author describes his experience in writing a scientific dialectological vocabulary starting from the raw materials collected by nonprofessionals. First he gives "bad" examples of materials of that kind as well as of procedures of reconsideration, correction and elimination. Then he discusses procedures for expansion of the collected material. All this is illustrated by examples from The Dictionary of Sveti Đurđ (The Dictionary of the Ludbreg Podravina region) that the author compiled together with Stjepan Belović, a local teacher and a devotee of the local Kajkavian dialect. He concludes that a first-rate scientific dictionary can be only written through collaboration between amateurs in the field and the professional expert, where the non-professional amateur by no means plays a minor role in the collaboration.